Early ileocolonoscopy with biopsy for the evaluation of persistent post-transplantation diarrhea - Bamias, Giorgos (Baishideng, 2010)
AIM: To investigate the significance of ileocolonoscopy with histology in the evaluation of post-transplantation persistent diarrhea (PD). METHODS: We retrospectively reviewed all records of renal transplant patients with PD, over a 3-year period. All patients were referred for ileocolonoscopy with biopsy, following a negative initial diagnostic work up. Clinical and epidemiological data were compared between cases with infectious or drug-induced diarrhea. RESULTS: We identified 30 episodes of PD in 23 renal transplant patients (1-3 cases per patient). There were 16 male patients and the mean age at the time of PD was 51.4 years. The average time from transplantation to a PD episode was 62.3 ± 53.2 mo (range 1-199 mo). Ileocolonoscopy detected mucosal abnormalities in 19 cases, whereas the intestinal mucosa appeared normal in 11 cases. Histological examination achieved a specific diagnosis in 19/30 cases (63.3%). In nine out of 11 cases (82%) with normal endoscopic appearance of the mucosa, histological examination of blinded biopsies provided a specific diagnosis. The etiology of PD was infectious in 11 cases (36.6%), drug-related in 10 (33.3%), of other causes in three (10%), and of unknown origin in six cases (20%). Infectious diarrhea occurred in significantly longer intervals from transplantation compared to drug-related PD (85.5 ± 47.6 mo vs 40.5 ± 44.8 mo, P < 0.05). Accordingly, PD due to drug-toxicity was rarely seen after the first year post-transplantation. Clinical improvement followed therapeutic intervention in 90% of cases. Modification of immunosuppressive regimen was avoided in 57% of patients. CONCLUSION: Early ileocolonoscopy with biopsies from both affected and normal mucosa is an important adjunctive tool for the etiological diagnosis of PD in renal transplant patients.